Peran Penggunaan Media Sosial dalam Pendidikan Antikorupsi bagi Generasi Muda - Muhammad Khoirur Rohman; Sausan Nadhifatul Kamilah; Ramadhina Lailatul Fitria (Jurnal Pendidikan dan Kewarganegara Indonesia, 2026)
Corruption remains a major challenge in Indonesia, highlighting the need for preventive efforts, one of which is through anti-corruption education. The advancement of technology has positioned social media as an effective platform to promote anti-corruption values to the young generation, who represent the largest group of social media users. This study aims to examine the role of social media as an educational medium for anti-corruption among the young generation, covering their level of engagement, the impacts, and the challenges encountered in its implementation. The study employs a literature review method by utilizing relevant academic sources, such as books and articles related to the research topic. The results indicate that social media is actively used by the young generation and effectively serves as a social sanction, while also enhancing awareness, encouraging participation, and disseminating anti-corruption education. However, its effectiveness is constrained by several challenges, including the spread of misinformation, limited digital literacy, negative responses from authorities, and unequal access to digital infrastructure. Therefore, collaboration between the government and society is essential to maximize the potential of social media as an optimal platform for anti-corruption education.